THE USE OF EUPHEMISMS IN UZBEK LITERATURE (Scientific journal of the Fergana State University, 2025)
This article discusses the use of euphemisms in literary works as a means to enhance the aesthetic power of language and to express ideas in a delicate and subtle manner. Euphemisms increase the emotional impact of the texts and allow writers to convey harsh or unpleasant themes in a softer way. In fiction, they are often employed when addressing topics such as death, illness, social issues, and other negative realities. Euphemisms are also used to portray human nature more deeply and to reflect the psychological state of characters. Through euphemisms, writers can gently introduce social problems into their works and encourage readers to view them from a new perspective.